Analysis of the Relationships between the Islamic Revolution of Iran and World Social Forum (WSF) in the Global Governance - hasan naserkhaki; ali morshedizad (رهیافتهای سیاسی و بین المللی)
Given the importance of the Islamic Revolution in the global arena and the growing importance of the role of new social movements in the field of global governance, this article seeks to examine the fundamental question of What is the relationship of the World Social Forum with the Islamic Revolution and what effect does it have on the advancement of the Islamic Revolution in the field of global governance? The answer to this question requires examining the bilateral relations between this movement and the Islamic Revolution. Therefore, according to theoretical basics about new social movements and using a qualitative method, this paper comparatively studied three components of identity, opposition, and totality in the Islamic Revolution and World Social Forum. For this purpose, first, with the technique of categorization and coding, the components of the Islamic Revolution and the World Social Forum have been extracted and then compared and proportioned The results indicated that regarding the identity component, the Islamic Revolution is more all-inclusive than the World Social Forum. Regarding the purpose and competitor components, although there are differences between the Islamic Revolution and the World Social Forum, significant similarities exist between them. Therefore, it is possible to harmonize and build capacity for synergy between them.